(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to identify the role of the dimensions of financial inclusion in achieving the competitive advantage by An exploratory research of the views of a sample of customers of the 20 Algerian commercial banks, And the relationship between its dimensions (Access dimension, Usage dimension, Quality) And competitive advantage. This research is based on the analytical descriptive approach. The questionnaire was adopted as a main tool in collecting data and information on the sample of 377. The The research showed several results, the most important of which is a strong correlation between the dimensions of the three financial inclusion combined and the competitive advantage of the Algerian commercial banks, and explained the (84%) of the changes in competitive advantage, And that the quality of financial services comes first in terms of importance and impact on the competitive advantage, as explained (69%) of the total impact on the competitive advantage.